Late Pleistocene stratigraphy of IODP Site U1396 and compiled chronology offshore of south and south west Montserrat, Lesser Antilles. (25th July 2014) - Wall‐Palmer, Deborah; Coussens, Maya; Talling, Peter J.; Jutzeler, Martin; Cassidy, Michael; Marchant, Isabelle; Palmer, Martin R.; Watt, Sebastian F. L.; Smart, Christopher W.; Fisher, Jodie K.; Hart, Malcolm B.; Fraass, Andrew; et al.
Abstract Marine sediments around volcanic islands contain an archive of volcaniclastic deposits, which can be used to reconstruct the volcanic history of an area. Such records hold many advantages over often incomplete terrestrial data sets. This includes the potential for precise and continuous dating of intervening sediment packages, which allow a correlatable and temporally constrained stratigraphic framework to be constructed across multiple marine sediment cores. Here we discuss a marine record of eruptive and mass‐wasting events spanning ∼250 ka offshore of Montserrat, using new data from IODP Expedition 340, as well as previously collected cores. By using a combination of high‐resolution oxygen isotope stratigraphy, AMS radiocarbon dating, biostratigraphy of foraminifera and calcareous nannofossils, and clast componentry, we identify five major events at Soufriere Hills volcano since 250 ka. Lateral correlations of these events across sediment cores collected offshore of the south and south west of Montserrat have improved our understanding of the timing, extent and associations between events in this area. Correlations reveal that powerful and potentially erosive density‐currents traveled at least 33 km offshore and demonstrate that marine deposits, produced by eruption‐fed and mass‐wasting events on volcanic islands, are heterogeneous in their spatial distribution. Thus, multiple drilling/coring sites are needed to reconstruct the full chronostratigraphy of volcanic islands. This multidisciplinary study will be vital to interpreting the chaotic records of submarine landslides at other sites drilled during Expedition 340 and provides a framework that can be applied to the stratigraphic analysis of sediments surrounding other volcanic islands.